ELEMEN DESAIN INTERIOR PADA VISUALISASI RUANG “PODCAST” - R. Haryadi Purnomo Raharjo (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
Podcasts have been growing into a new trend in the development of digital communication media in Indonesia. The public is interested in podcasts because the discussions presented are relaxed but informative. What is more, the podcasters as the owners and the hosts of the event are popular public figures in community. Podcasts usually take place in closed spaces or indoors which are instagrammable with their attractive and artistic interior design. It implies that podcast studios are built at great expense. The current study aims to examine interior design elements essential for the existence of a podcast studio based on the viewpoint, the principles of balance, elements of space, color, texture, lighting concepts, the use of furniture, and other elements to fill the space. Observation results of podcast studios’ artistic layout confirm that interior design elements are added values attached to the setting of the spaces. Remarkably, there is a tendency in interior display of podcast studios to expose contemporary lifestyles of the owners in conjunction with architecture development and urban interior design.